The Self-Acceptance and Quality of Life in Patients Undergoing Hemodialysis Therapy: A Literature Review - Putri, Prestasianita; Afandi, Alfid; Kurniawan, Dicky Endrian; Kurniawati, Yulia (Rajaki of Tulip Medika Publisher, 2024)
Hemodialysis is one of the therapies undertaken by chronic kidney failure sufferers. This therapy takes quite a long time and is carried out routinely to replace the work of the kidneys with a hemodialysis machine. Several variable components have been studied to determine the condition of hemodialysis patients. The variables of self-acceptance and quality of life are often related to the condition of hemodialysis patients, but there has been no research that directly links these two things. Therefore, this study aims to analyze the self-acceptance and quality of life of patients undergoing hemodialysis therapy. The method used in this research is literature review articles from article search engines such as PubMed, Google Scholar, and Science Direct, which were analyzed using the PRISMA technique by including articles published in the last 5 years. The results of the literature review found that there is a relationship between self-acceptance and the quality of life of patients undergoing hemodialysis. The research results for both variables provide linear results. Patients with good self-acceptance will have a better quality of life, too.